The Effect of Streamflow, Ambient Groundwater, and Sediment Anisotropy on Hyporheic Zone Characteristics in Alternate Bars. Issue 1 (26th January 2021) - Monofy, A.; Boano, F.
Abstract: The hyporheic exchange is the main driver for the biogeochemical transformations of nutrients within a river bed. The current study addresses the variations in hyporheic zone (HZ) characteristics in alternate bars due to different streamflow, ambient groundwater, and sediment anisotropy. Several simulations, using a sequentially coupled surface water‐groundwater model of a synthetic reach with fully developed alternate bars morphology, were performed. Two HZs exist within the streambed; a shallow zone that is more linked to surface water, and a deep one that is more influenced by the groundwater variations. Increasing streamflow, and therefore bar submergence, decreases the hyporheic flow. The residence times distribution is bimodal, which implies the existence of two HZs . This bimodality is enhanced by anisotropic sediment conditions, while it is much milder in isotropic ones. The shallow zone residence times increase when streamflow value rises, while the residence times in the deep HZ are less affected. The mean and median residence times decrease by increasing streamflow in partially submerged case, and they are larger in fully submerged case. The hyporheic flow, area, residence times, and extent decrease by increasing groundwater fluxes. The deep zone is the most affected by the groundwater fluxes. Hyporheic flow and extent values are significantly larger in isotropic conditions than in anisotropic ones. The change in residence times values is different between the deep and shallow zones. A predictive model is driven to predict the hyporheic flux, residence times, and hyporheic depths dependence on bar submergence, ambient groundwater, and sediment anisotropy. Key Points: Shallow and deep hyporheic zones (HZs) exist in alternate bars with different characteristics The residence times distribution exhibit different level of bimodality A predictive model is presented to estimate the variations in HZ characteristics with streamflow and ambient groundwater variations and sediment anisotropy